An emergency department medical record review for adolescent intentional self-harm injuries - Hansen, Anna (Inj Epidemiol, 2021)
BACKGROUND: Non-suicidal self-injury and suicide attempts are increasing problems among American adolescents. This study developed a definition for identifying intentional self-harm (ISH) injuries in emergency department (ED) records coded with International Classification of Diseases, 10th Revision, Clinical Modification (ICD-10-CM) codes. The definition is based on the injury-reporting framework proposed by the Centers for Disease Control and Prevention. The study sought to estimate the definition’s positive predictive value (PPV), and the proportion of ISH injuries with intent to die (i.e., suicide attempt). METHODS: The study definition, based on first-valid external cause-of-injury ICD-10-CM codes X71-X83, T14.91, T36-T65, or T71, captured 207 discharge records for initial encounters for ISH in one Kentucky ED. Medical records were reviewed to confirm provider-documented diagnosis for ISH, and identify intent to die or suicide ideation. The PPV of the study definition for capturing provider-documented ISH injuries was reported with its 95% confidence interval (95% CI). RESULTS: The estimated PPV for the study definition to capture ISH injuries was 88.9%, 95% CI (83.8%, 92.8%). The estimated percentage of ISH with intent to die was 45.9, 95% CI (47.1, 61.0%). The ICD-10-CM code “suicide attempt” (T14.91) captured only 7 cases, but coding guidelines restrict assignment of this code to cases in which the mechanism of the suicide attempt is unknown. CONCLUSIONS: The proposed case definition supported a robust PPV for ISH injuries. Our findings add to the evidence that the current ICD-10-CM coding system and coding guidelines do not allow identification of ISH with intent to die; modifications are needed to address this issue.